Optimal Block Diagonalization precoding scheme for MU-MIMO Downlink channel Using Particle Swarm Optimization - Saxena, Shivangini; R.P. Singh, Dr (International Journal of Engineering and Technology, 2018)
As wireless communication turns out to be more common, the interest for higher rates of data transfer and continuous availability is expanding. Future wireless systems are provisioned to be very heterogeneous and interconnected. Higher data rates and Quality of Service (Qos) are two major expectations from any wireless technology. Fading is the main phenomenon which restricts the realization of Qos demand and higher data rates in wireless technologies. Fading is caused by obstacles in signal path which degrades the received signalâ€™s quality. To mitigate the impact of fading on communication system the application of precoding techniques can be used. In this regard, this paper presents optimization of Block-Diagonalization (BD) based linear precoding scheme for multi-user multiple-input multiple output (MU-MIMO) systems. Simulation environment consists of a MIMO downlink scenario where a single base station (BS) with Â antennas transmits to K receivers each with Â antenna. The application of Particle Swarm Optimization (PSO) is used to find the optimal number of received antennas so as to reduce system complexity while maintaining Bit Error Rate (BER) performance of the system. MATLAB based simulation scenario is presented and evaluated over Rayleigh fading environment. Simulation results validate that the performance of Blockâ€“ Diagonalization scheme can be improved up to 5dB with the application of Particle Swarm Optimization technique. Â